Aktivitas Fisik, Kebahagiaan, dan Kesejahteraan Psikologis: Tinjauan Literatur dari Perspektif Filsafat Olahraga - Dinata, Windo Wiria; Fitri, Mustika; Sucipto, Sucipto; Rismayadi, Alen; Andria, Yogi (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Physical activity is an important factor that contributes to physiological health, as well as the psychological well-being of an individual. Participation in sport has increasingly been associated with higher levels of happiness, subjective well-being, and the development of meaning in life. However, the philosophical dimensions of sport participation remain relatively underexplored within the field of sport science literature. This study aims to examine the relationship between sport participation, happiness, and meaning in life through a narrative literature review approach. The literature search was conducted across several international academic databases, including Google Scholar, Scopus, and Web of Science, using keywords related to physical activity, psychological well-being, happiness, and meaning in life. Approximately 40 relevant scientific publications were analyzed thematically to identify psychological and philosophical mechanisms linking sport participation to human well-being. The findings indicate that physical activity contributes to happiness through several mechanisms, including the enhancement of subjective well-being, the strengthening of self-efficacy, emotional regulation, and the fulfillment of basic psychological needs as described in Self-Determination Theory. In addition, experiences of challenge, achievement, and social engagement in sport play a significant role in helping individuals develop a sense of meaning in life. Therefore, sport should not only be viewed as a physical activity aimed at improving bodily health but also as an important medium for fostering psychological well-being and meaningful living. These findings highlight the importance of promoting sport participation within society as part of a broader strategy to improve overall quality of life.